Post- surgical outcomes and prognosis of intentionally replanted lower posterior teeth - Wafaa k Abid (Al-Rafidain Dental Journal, 2010)
Aims: To evaluate intentional replantation based on clinical and radiographic assessment criteria over a two year period. Materials and Methods: The clinical trial was conducted at the Department of Oral and Maxillofacial Surgery/ College of Dentistry/ Mosul University. Twenty lower posterior teeth in twenty patients of different ages and genders were enrolled in the trial. Each patient was subjected to a standard surgical protocol for intentional replantation. The criteria evaluated were both clinical and radiographical on scheduled visits for two years for each patient. Clinical criteria included pain level, tooth mobility and sinus formation. Radiographical criteria were periapical radiolucency ,root resorp-tion and ankylosis. Results: In regard to clinical criteria, no significant statistical difference was dis-closed for pain score levels and sinus formation at the scheduled visits. However, significant difference was recorded for tooth mobility at different interval visits. For radiographic criteria , a significant dif-ference for periapical radiolucency, root resorption and ankylosis was recorded at interval visits. Con-clusion: The success of intentional replantation is likely dependent upon a minimally traumatic ex-traction, short extra-oral time with copious irrigation and meticulous instrumentation as well as careful-ly controlled postoperative patient compliance. The clinical and radiographic results of cases in the current trial were satisfactory. Further study on a much more post-operative period( more than two years) and the use of materials to improve the success of intentional replantation is encouraged.